2016
DOI: 10.1016/j.csbj.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Developing a mobile application to better inform patients and enable effective consultation in implant dentistry

Abstract: The field of dentistry lacks satisfactory tools to help visualize planned procedures and their potential results to patients. Dentists struggle to provide an effective image in their patient's mind of the end results of the planned treatment only through verbal explanations. Thus, verbal explanations alone often cannot adequately help the patients make a treatment decision. Inadequate attempts are frequently made by dentists to sketch the procedure for the patient in an effort to depict the treatment. These at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Although some previous studies used smartphone apps as instructional tools, 10,19 others have utilized these apps as reminders. 5,20 Many studies have reported results similar to ours: Zotti et al 1 assessed the efficacy of a WhatsApp-based program that was a combination of oral hygiene maintenance during orthodontic treatment and using a chat room known as "Brush Game."…”
Section: Discussionmentioning
confidence: 99%
“…Although some previous studies used smartphone apps as instructional tools, 10,19 others have utilized these apps as reminders. 5,20 Many studies have reported results similar to ours: Zotti et al 1 assessed the efficacy of a WhatsApp-based program that was a combination of oral hygiene maintenance during orthodontic treatment and using a chat room known as "Brush Game."…”
Section: Discussionmentioning
confidence: 99%
“…In Balsamiq Mockups, mobile applications are designed in a more intelligent and easy way [18], they are also used to design the structure, hierarchy and relationship between the elements that compose the mobile application [19]. Future integration will be done with Android Studio IDE, and there are several methods to make a mobile application.…”
Section: About the Methodologymentioning
confidence: 99%
“…59.6% of the world population are using internet, and 70.2% of the Middle East population were recorded using internet applications [23]. The availability and ease of using smart applications (apps) by mostly all categories of the population encourages the idea of their benefit in dental health care and education [24].…”
Section: Smart Applications In Modern Dentistrymentioning
confidence: 99%
“…They as well, facilitated information exchange in which dentists can receive clinical information captured by the patients and delivered as text, voice recording, or high-resolution photographs [27]. Using interactive apps, practitioners are able to demonstrate visually and interactively the detailed state of the patient's dental health, and proposed treatment [24,28]. Smart apps enhanced patients motivation and education, and provided a feasible means for consultations and health advice [29].…”
Section: Smart Applications In Modern Dentistrymentioning
confidence: 99%